Development and Programmed Cell Death in the Filament Cells of Lathyrus undulatus Boiss. - (:unkn) unknown (UNIV FLORENCE BOTANY INST, 2011)
The androecium in Lathyrus undulatus Boiss. consisted of 10 stamens. The anther was joined to the filament on the outward facing surface (dorsifixed). After dehiscence anther and filament separate from connecting edge and anther falls off. In the present study development and programmed cell death process in the filament cells of Lathyrus undulatus Boiss. (Fabaceae) were analyzed by light, fluorescence and electron microcopy, during pollen development. The observations indicated that filament cells most fully developed at tetrad stage. The cytochemical identifications of proteins, insoluble polysaccharides and lipids within and around the vascular bundle suggest that filament cells are involved in the transport of the organic materials. Moreover, filament cells subject to programmed cell death confirmed with TUNEL from young to mature pollen stage including structural alterations such as nucleus and chromatin condensation, vacuolization, concentric circle of membranes and disintegrated plastids. Granular materials and electron lucent areas in the cytoplasm were common at mature pollen stage. The attained data suggests that degenerated anther separate from filament by programmed cell death of the connecting edge.
Keywords: cytochemistry; Fabaceae; filament; Lathyrus undulatus Boiss.; programmed cell death; ANTHER DEHISCENCE; POLLEN GRAINS; MATURATION; PRINCIPLES; APOPTOSIS; ENZYME; MUTANT; PCD